HUBUNGAN PRE-EKLAMSI DENGAN BERAT BAYI LAHIRDI RUANG BERSALIN RUMAH SAKIT UMUM DAERAHDr. WAHIDIN SUDIRO HUSODO MOJOKERTO - Nur So’emah, Eka; Nur Fitriyana, Ifa (JURNAL KEPERAWATAN SEHAT, 2016)
Maternal Mortality and The Infant Mortality Rate is an indicator of the success of development in the field of health. Preeclampsia is a major causeof mortality and morbidity in the mother and baby with a high number of cases of small infants (low birth weight) for pregnancy and is responsible for 30-50% of perinatal deaths Indonesia. The research objective was to determine the relationship of preeclampsia with birth weight in RSUDDr.Wahidin Sudiro Husodo Mojokerto. The study design using analytic correlation with retrospective approach. The Population of all patients with preeclampsia in RSUD Dr.Wahidin Sudiro Husodo Mojokerto in 1stDecember 2014 until 18stMay 2015 by43 mothers so the researchers decided took this all members of the population being sampled is sampling jenuh.Data taken with the observation data recore on the checklist sheet restrospektive patient medical records. After the data collected do data processing editing, coding, scoring and tabulating continued presentation of data Cross Tabulating Tabel with distribusi frekuension the program SPSS 20 for Windows. The results showed that patients with the greatest risk of preeclampsia/eclampsia give birth to low birth weight (46,5%) a total of 20 respondents from 43 respondents so the meaning that there is a relationship preeclampsia with birth weight in RSUD Dr.Wahidin Sudiro Husodo Mojokerto which shows significant relationship. Mothers who experienced preeclampsia during pregnancy have a greater risk of 4,164 to give birth to babies with low birth weight because the mother preeclampsia decreased utero placental perfusion, hipovolemia, vasospasme and damage to the endothelial cells of blood vessels of the placenta that can cause chronic hypoxia in the fetus and fetal growth retardation so as to expire on babies born with severe disorder greatest risk of low birth weight.Keywords : Preeclampsia, Birth Weight